Validation and psychometric properties of the Persian version of the MISSCARE survey - Shoeleh Rahimi; Abbas Ebadi; Hamid Reza Khankeh; Mohammad Eghbali; Azam Sharifi; Batol Mohammadian; Mohammad Sajjad Lotfi (Wiley, 2023)
Abstract Aim To conduct, translate, and psychometric evaluation of the MISSCARE‐Persian Survey. Design A cross‐sectional study was conducted in Iran in February-June 2021. Methods The translation of the MISSCARE Survey was accomplished according to World Health Organization (WHO) guidelines. Construct validity was performed by (N = 300) exploratory factor analysis and confirmation. To assess the reliability, internal consistency was assessed using Cronbach's alpha coefficient, and relative stability was assessed using the interclass correlation coefficient (ICC). The study adhered to COSMIN guidelines. Results The exploratory factor analysis, which resulted in the identification of three factors in the second part of the tool, explained 79.6% of the total variance. Confirmatory factor analysis indicated the model's good fit of information. The reliability of the first and second parts of the tool was 0.912 and 0.901, respectively. Additionally, the ICC was found to be 0.687 for the first and 0.706 for the second part of the tool.